Analysis of the Effect of Production Factors Gillnet in the Waters of East Tanjung Jabung Regency - M. Hariski; Zulkifli Alamsyah; Saad Murdy (Berkala Perikanan Terubuk, 2022)
Research on the analysis of the influence of production factors on gillnet catches in the waters of Tanjung Jabung Timur is located at the Fish Landing Base, Nipah Panjang District. This study aims to identify and analyze the effect of production factors on gillnet catches in the waters of Tanjung Jabung Timur Regency. The research method used was a survey, the sampling method was simple random sampling and the analytical method used was the Cobb-Douglas production function. The results showed that the production factors that had a significant effect on increasing gillnet catches in the waters of Tanjung Jabung Timur Regency were shipped GT, engine PK, fishing gear length, amount of fuel, the number of crew members, and fishing experience.